Pemikiran Syed Muhammad Naquib al-Attas tentang Konsep Ta'dib dalam Membentuk Manusia Beradab: Syed Muhammad Naquib al-Attas's Thoughts on the Concept of Ta'dib in Forming Civilized Humans - Rachmadianti, Irma; Haryanto, Budi (Tasfiyah: Jurnal Pemikiran Islam, 2025)
This study aims to explore the concept of Islamic education according to Syed Muhammad Naquib al-Attas and t to examine its relationship with reason and the Al-Qurâ€™an. This research employs a literature research method by collecting data through the process of text analysis from various literary sources. The results of the research show that the concept of Islamic education offered by al-Attas is ta'dib. Ta'dib can be understood as an effort to influence and instill (inculcate) manners in humans which is carried out through the educational process. This concept focuses on instilling manners in students so that they are able to become good and civilized human beings. In order to be a good and civilized human being, a person must be able to differentiate between good and bad. In this context, al-Attas explained that the reason and the values â€‹â€‹of the Al-Qur'an are two important things so that humans can differentiate between what is á¸¥aqq and bÄthil. Al-Attas revealed that reason and the Al-Qurâ€™an are two things that complement each other.